Cross-sectional descriptive study of management modalities and quality of life of surgical patients in a palliative care unit - Yan, Naing Soe; Amjad, Nasser Muhammad; Karim, K.A. (The Faculty of Medicine, International Islamic University Malaysia, 2016)
The goal of palliative care is the provision of the best quality of life (QOL) for terminally ill and dying patients. Advances in medical treatment has seen an increase in overall survival of all stages of malignant diseases. This includes advanced and/or inoperable malignancies where management is mainly palliative involving different modalities. Methods: We designed a cross-sectional descriptive study of surgical patients in a palliative care unit in a 1000-bedded teaching hospital in Kuantan, Malaysia. Objectives of this study are: to study the demographic characteristics and indications for admission of surgical patients in palliative care unit, to study the options of treatment modalities and their complications, to identify the barriers in decision making in surgical treatment and finally to objectively assess the quality of life of these patients by utilizing QUALITY OF LIFE (WHOQOL) –BREF –questionnaire. Results: One hundred and one eligible patients (53%) male, (47%) female of mean age of 54yrs, majority Malay and Chinese patients were included in the study. All patients had malignancies and they were Breast (30%), Lower gastrointestinal (GI) (24%), (18%) upper GI, (15%) hepato-biliary, and (7%) pancreatic cancers. Thirty two percents of patients had emergency treatment while the rest had supportive treatment. Barriers to decision making were mainly due to patient factors in 71%, while 12% was due to the disease presenting at an advanced stage and 15% due to limitation of care. The final results of overall quality of life rating were shown as poor (1%), neither poor nor good (42%), good (52%) and very good (2%). Conclusions: Palliative care and end of life decision making from surgical point of view is a delicate issue. Like all other fields in medicine, palliative care must be evidence-based with specific goal directed therapy. Our study shows that we are able to positively impact the quality of life in more than two thirds of our patients. Our aim is to achieve 100% success. As such, it is imperative to inculcate the goal of palliative care to all grades of health care personnel. ‘To cure sometimes, To relieve often, To comfort always’ should not be mere words.